2022
DOI: 10.1186/s12933-022-01672-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cardiovascular disease in patients with metabolic-associated fatty liver disease: a machine learning approach

Abstract: Background Nonalcoholic fatty liver disease is associated with an increased cardiovascular disease (CVD) risk, although the exact mechanism(s) are less clear. Moreover, the relationship between newly redefined metabolic-associated fatty liver disease (MAFLD) and CVD risk has been poorly investigated. Data-driven machine learning (ML) techniques may be beneficial in discovering the most important risk factors for CVD in patients with MAFLD. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Finding the difference in IMT only might seem to be an accidental finding and it certainly requires further research. However, in our previous study in which we exploited machine learning methods, we found that the plaque score of the right carotid artery, among others, can identify patients with metabolic-associated fatty liver disease and prevalent CVD [50].…”
Section: Discussionmentioning
confidence: 99%
“…Finding the difference in IMT only might seem to be an accidental finding and it certainly requires further research. However, in our previous study in which we exploited machine learning methods, we found that the plaque score of the right carotid artery, among others, can identify patients with metabolic-associated fatty liver disease and prevalent CVD [50].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that a model with few predictors is preferred, as it is less costly and time-consuming to use (43). To address this concern, many choose to employ data-driven feature selection approaches, e.g., (44) to remove non-informative features from models. Methods for data-driven feature selection include wrapper methods, which evaluate multiple models by adding and/or removing features to optimize model performance, and filter methods, which assess the relevance of features separately from the predictive models and only include predictors that meet specified criteria in the final model (43).…”
Section: Feature Selectionmentioning
confidence: 99%
“…Developing a high-quality systematic review is of great value to the disease’s diagnosis, treatment, and prevention ( 16 ). Therefore, trials have been published in cardiovascular diabetology ( 2 , 10 12 ). However, because the results of cardiovascular diabetes are complicated, the reported outcomes are also different in trials ( 2 , 10 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, trials have been published in cardiovascular diabetology ( 2 , 10 12 ). However, because the results of cardiovascular diabetes are complicated, the reported outcomes are also different in trials ( 2 , 10 12 ). In some trials, cardiovascular events were subjectively reported by the patients, and insufficient and under-reported problems always existed ( 1 , 12 ).…”
Section: Introductionmentioning
confidence: 99%